2020
DOI: 10.1101/2020.09.10.290916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wheat developmental traits as affected by the interaction betweenEps-7Dand temperature under contrasting photoperiods with insensitivePpd-D1background

Abstract: Earliness per se (Eps) genes are important to fine tune adaptation, and studying their probable pleiotropic effect on wheat yield traits is worthwhile. In addition, it has been shown that some Eps genes interact with temperature. We studied two NILs differing in the newly identified Eps-7D but carrying insensitive Ppd-D1 in the background under three temperature regimes (9, 15 and 18 °C) and two photoperiods (12 h and 24 h). Eps-7D affected time to anthesis as expected and the Eps-7D-late allele extended both … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 67 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…The fact that the Eps-7D × Ppd-D1 interactions would be clearer at some temperatures as opposed to others is also something that could have been expected as both Eps-7D [ 1 ], as well as other Eps [ 7 , 9 , 14 , 15 , 34 , 35 ], and Ppd genes [ 12 , 36 , 37 ] have shown to interact with temperature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The fact that the Eps-7D × Ppd-D1 interactions would be clearer at some temperatures as opposed to others is also something that could have been expected as both Eps-7D [ 1 ], as well as other Eps [ 7 , 9 , 14 , 15 , 34 , 35 ], and Ppd genes [ 12 , 36 , 37 ] have shown to interact with temperature.…”
Section: Discussionmentioning
confidence: 99%
“…This Eps-7D interacted with temperature [ 1 ] and Eps-2B [ 16 ], and the interaction effect have been shown to be effective well beyond the duration of developmental phases. Our findings suggest that it is not only important to study every newly identified Eps gene (simply because although they are all named equally, the mechanisms by which they actually modify time to anthesis may be quite different), but it is also necessary to evaluate their functions under varying backgrounds of other important genetic factors affecting wheat development to ensure repeatability of their effect and their application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations